2014
DOI: 10.1097/ppo.0000000000000052
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome and Colorectal Carcinoma

Abstract: The mammalian microbiota plays a crucial role in the pathogenesis of many diseases. Thanks to recent advances in metagenomics, proteomics, and metabolomics, microbiome composition and metabolic activity can now be studied in detail. Results obtained by such fascinating and provocative studies would be meaningless without considering the perspective of the whole organism. Our work using gnotobiology as the major tool to unravel the mechanisms of host-microbe interaction has demonstrated the crucial role of micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 115 publications
0
17
0
2
Order By: Relevance
“…This finding may indicate that an inflammatory environment could promote in vivo CRC tumor growth. Previous studies have demonstrated that inflammatory processes are associated with CRC tumorigenesis [47][48][49], and that the microbiota has the potential to shape the inflammatory microenvironment in the intestine [50].…”
Section: Discussionmentioning
confidence: 99%
“…This finding may indicate that an inflammatory environment could promote in vivo CRC tumor growth. Previous studies have demonstrated that inflammatory processes are associated with CRC tumorigenesis [47][48][49], and that the microbiota has the potential to shape the inflammatory microenvironment in the intestine [50].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Swidsinski et al demonstrated the relationship between abundance of E. coli and CRC tumorigenesis early in 1998[ 27 ]. It is conceivable that intestinal microbiota plays a key role in the beginning of CRC with mounting evidence [ 28 31 ]. According to what had been founded in NCM460 and HCT116 cell lines, we suspected that in APC mutation population, ethanol was a risk factor for development of colorectal cancer, which might contribute to allowing gram-negative bacteria LPS into the blood, and activate TLR4/NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that the gut microbiome plays a role in CRC development. Experimental proof of gut microbiota involvement in CRC development came from gnotobiotic animal models ( Reddy et al, 1975 ; Vannucci et al, 2008 ; Arthur and Jobin, 2011 ; Klimesova et al, 2013 ; Tlaskalova-Hogenova et al, 2014 ). Recent studies using next generation sequencing and polymerase chain reaction have shown that Fusobacterium nucleatum is frequently detected in stool and biopsy samples from CRC patients ( Castellarin et al, 2012 ; Kostic et al, 2012 ; Flanagan et al, 2014 ).…”
Section: Oral Microbiota and Colorectal Carcinogenesismentioning
confidence: 99%